Discovery and SAR of 4-aminopyrrolidine-2-carboxylic acid correctors of CFTR for the treatment of cystic fibrosis. (15th September 2022) - Scanio, Marc J.C.; Searle, Xenia B.; Liu, Bo; Koenig, John R.; Altenbach, Robert J.; Gfesser, Gregory A.; Bogdan, Andrew; Greszler, Stephen; Zhao, Gang; Singh, Ashvani; Fan, Yihong; Swensen, Andrew M.; et al.
Graphical abstract: Abstract: Cystic fibrosis (CF) is an autosomal recessive disease resulting from mutations on both copies of the CFTR gene. Phenylalanine deletion at position 508 of the CFTR protein (F508del-CFTR) is the most frequent mutation in CF patients. Currently, the most effective treatments of CF use a dual or triple combination of CFTR correctors and potentiators. In triple therapy, two correctors (C1 and C2) and a potentiator are employed. Herein, we describe the identification and exploration of the SAR of a series of 4-aminopyrrolidine-2-carboxylic acid C2 correctors of CFTR to be used in conjunction with our existing C1 corrector series for the treatment of CF.